Aqueous zinc ion battery cathode current collector and production method thereof

The ternary alloy negative electrode current collector prepared through vacuum smelting and annealing treatment solves the problems of zinc negative electrode dendrites, improves the circulation performance and life of zinc ion batteries, is suitable for large-scale production and reduces costs.

CN119265449APending Publication Date: 2025-01-07SONGSHAN LAKE MATERIALS LAB +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411291777.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The zinc negative electrode has problems with dendrite growth, hydrogen evolution reaction and corrosion passivation in aqueous zinc ion batteries, resulting in low zinc deposition efficiency and limited cycle life.

Method used

The ternary alloy negative electrode current collector prepared by vacuum smelting, rolling and annealing treatment includes 83.1 to 90.6% copper, 9.1 to 16.6% zinc and 0.2 to 0.4% tin to form a single-phase structure and solid-soluble structure, promotes uniform zinc deposition.

Benefits of technology

It improves the Coulomb efficiency and charging and discharging efficiency of zinc ion batteries, extends the cycle life of the battery, and is suitable for large-scale production, with simple processes and low production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265449A_ABST
    Figure CN119265449A_ABST
Patent Text Reader

Abstract

The invention discloses an aqueous zinc ion battery negative electrode current collector, which is prepared through vacuum melting, rolling and annealing treatment, and comprises the following components in percentage by mass: 83.1-90.6 wt% of copper, 9.1-16.6 wt% of zinc, 0.2-0.4 wt% of tin and inevitable impurity elements. Uniform zinc deposition can be induced in the zinc deposition process, the coulombic efficiency of the battery is improved, the charge and discharge efficiency is improved, the cycle performance is improved, the cycle life of the battery is prolonged, and the method is suitable for large-scale production, simple in process and low in production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of negative electrode materials for aqueous zinc ion batteries, and in particular to a negative electrode current collector for aqueous zinc ion batteries and a production method thereof. Background Art

[0002] Lithium-ion batteries are widely used in consumer electronics and electric vehicles due to their high energy density, long cycle life, low self-discharge, no memory effect, and low environmental impact. However, the shortage of lithium resources and safety issues of lithium-ion batteries have prompted people to develop a new type of secondary battery that is safe, environmentally friendly, and low-cost.

[0003] Compared with organic electrolyte batteries, aqueous batteries are considered more promising due to their non-flammability, low cost, and good rate performance. Among them, the zinc metal negative electrode has a high theoretical capacity (820mAh / g), a low redox potential (-0.76V), and a high hydrogen evolution overpotential. Therefore, aqueous zinc-ion batteries show great application potential in large-scale energy storage systems.

[0004] At present, the main problems of zinc negative electrode are manifested in three aspects: negative electrode dendrite growth, hydrogen evolution reaction (HER) and corrosion passivation. This series of problems directly or indirectly causes zinc deposition, low stripping efficiency and limited cycle life.

[0005] In recent years, various effective strategies have been proposed to solve the problems related to zinc negative electrodes. Among them, alloying modification of negative electrode current collectors is considered to be one of the feasible strategies to reduce the impact of negative electrode problems. Compared with laboratory-level surface coating, three-dimensional structure and other negative electrode current collector modifications, the synthesis method of alloy current collectors is more suitable for large-scale production. Therefore, it is necessary to develop a multi-element alloy current collector with a more comprehensive optimization effect to improve the performance of zinc negative electrodes in aqueous zinc-ion batteries. Summary of the invention

[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide an aqueous zinc ion battery negative electrode current collector, wherein the ternary alloy prepared by vacuum melting, rolling and annealing treatment comprises 83.1-90.6wt% of copper, 9.1-16.6wt% of zinc, 0.2-0.4wt% of tin and inevitable impurity elements by mass percentage,

[0007] The ternary alloy has a single-phase structure, the alloy elements exist in the form of solid solution, zinc and tin are solid-solved in the alloy matrix, a large number of equiaxed crystals and a small amount of twins are distributed inside the grains, the grain size is 7 to 10 μm, the twin area fraction is 1.2 to 4.5%, and XRD characterization shows no characteristic peaks other than copper and zinc.

[0008] A further technical solution comprises, by mass percentage, 83.1-90.6wt% of copper, 9.1-16.6wt% of zinc, 0.3wt% of tin, and inevitable impurity elements.

[0009] A further technical solution is to take 906g of copper, 91g of zinc and 3g of tin in weight proportion, and prepare Cu-9.1Zn-0.3Sn, the negative electrode collector of an aqueous zinc ion battery, through vacuum melting, rolling and annealing. The zinc and tin elements are dissolved in the alloy matrix, and the grain size is 7 to 10μm. A large number of equiaxed crystals and a small amount of twins are distributed inside the grains, and the twin area fraction is 1.2 to 4.5%.

[0010] A further technical solution is to take 831g of copper, 166g of zinc and 3g of tin by weight, and prepare Cu-16.6Zn-0.3Sn, the negative electrode collector of an aqueous zinc ion battery, through vacuum melting, rolling and annealing. The zinc and tin elements are dissolved in the alloy matrix, and the grain size is 7 to 10μm. A large number of equiaxed crystals and a small amount of twins are distributed inside the grains, and the area fraction of twins is 1.2 to 4.5%.

[0011] The method for producing a negative electrode current collector for an aqueous zinc ion battery comprises the following steps:

[0012] Step S1: Vacuum melting,

[0013] 83.1-90.6wt% of metal copper, 9.1-16.6wt% of metal zinc, and 0.2-0.4wt% of metal tin are placed in a graphite crucible, preferably 83.1-90.6wt% of metal copper, 9.1-16.6wt% of metal zinc, and 0.2-0.4wt% of metal tin are placed in a graphite crucible, and a vacuum melting furnace is used for vacuum melting treatment, and the vacuum degree during the vacuum melting process is 10-20°C. -5 mbar, the melting temperature in the vacuum melting process is 500~1100℃, and the melting time in the vacuum melting process is 0.5~2h.

[0014] After cooling to room temperature, an alloy ingot is obtained;

[0015] Step S2: Cutting, cutting the alloy ingot into alloy sheets with a thickness of 3 to 30 mm.

[0016] Step S3: rolling-annealing,

[0017] The alloy sheet is subjected to rolling treatment to obtain an alloy foil with a thickness of 90 to 150 μm. The alloy foil is subjected to annealing treatment after the rolling treatment. The annealing temperature is 400 to 500° C. and the annealing time is 4 to 5 hours. After the annealing treatment is completed, the alloy foil is naturally cooled to room temperature in an argon and hydrogen atmosphere to obtain an aqueous zinc ion battery negative electrode collector with a thickness of 90 to 150 μm. The aqueous zinc ion battery negative electrode collector is a ternary alloy, including an aqueous zinc ion battery negative electrode collector Cu-9.1Zn-0.3Sn and an aqueous zinc ion battery negative electrode collector Cu-16.6Zn-0.3Sn.

[0018] Compared with the prior art, the advantages of the present invention are as follows: the preparation method of the present invention adopts the negative electrode current collector obtained by the smelting-rolling method, which can induce uniform zinc deposition during the zinc deposition process, improve the battery coulomb efficiency, improve the charge and discharge efficiency, improve the cycle performance, and extend the battery cycle life; the present invention is suitable for large-scale production, has a simple process, and has a low production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a flow chart of the preparation of the negative electrode current collector in the present invention;

[0020] Figure 2 XRD diagram of the negative electrode current collector in Examples 1 and 3 of the present invention;

[0021] Figure 3 The SEM image and element distribution diagram of the Cu-9.1Zn-0.3Sn negative electrode current collector in Example 1 of the present invention;

[0022] Figure 4 This is a schematic diagram of the assembly of a half-cell in the present invention;

[0023] Figure 5 This is a half-cell cycle diagram of the Cu-9.1Zn-0.3Sn negative electrode current collector in Example 2 of the present invention;

[0024] Figure 6 The SEM image and particle size distribution diagram of the Cu-16.6Zn-0.3Sn negative electrode current collector in Example 3 of the present invention;

[0025] Figure 7 This is a half-cell cycle diagram of the Cu-16.6Zn-0.3Sn negative electrode current collector in Example 3 of the present invention;

[0026] Figure 8 This is a half-cell cycle diagram of the Cu current collector in Comparative Example 1 of the present invention; DETAILED DESCRIPTION

[0027] Example 1

[0028] Preparation method of Cu-9.1Zn-0.3Sn negative electrode current collector for aqueous zinc ion battery, Figure 1 As shown, the following steps are included:

[0029] (1) Weigh 906 g of copper, 91 g of zinc, and 3 g of tin respectively;

[0030] (2) placing metal copper, zinc and tin into a graphite crucible, smelting them in a vacuum device at 1100° C. for 1 h, and then pouring and cooling to room temperature to obtain a Cu-9.1Zn-0.3Sn alloy ingot;

[0031] (3) Cutting the Cu-9.1Zn-0.3Sn alloy ingot into 3 mm thick alloy sheets;

[0032] (4) After the alloy sheet was rolled to 90 μm at one time, it was annealed at 450°C for 4 h and naturally cooled to room temperature in an argon and hydrogen atmosphere to prepare the Cu-9.1Zn-0.3Sn negative electrode current collector for the ternary alloy aqueous zinc ion battery.

[0033] The prepared aqueous zinc ion battery negative electrode current collector Cu-9.1Zn-0.3Sn was subjected to XRD and SEM tests. Figure 2 , 3 As shown, there are a large number of equiaxed crystals distributed in the grains, the grain size is 7 to 10 μm, and there are no characteristic peaks other than copper and zinc in the XRD diagram, that is, the alloy has a single-phase structure, which is consistent with the SEM results, and it is judged that the alloy ultimately exists in the form of solid solution.

[0034] Example 2

[0035] The aqueous zinc ion battery negative electrode current collector Cu-9.1Zn-0.3Sn prepared in Example 1 was tested.

[0036] Weigh 5.75g ZnSO4·7H2O, add 7.48mL deionized water to prepare 2M ZnSO4 electrolyte. Figure 4 As shown in the figure, the prepared aqueous zinc ion battery negative electrode current collector Cu-9.1Zn-0.3Sn and commercial zinc foil were assembled into a half-cell. -2 , 1mAh cm -2 The coulombic efficiency and cycle stability were tested under the following conditions: Figure 5 As shown in the figure, the half-cell assembled with Cu-9.1Zn-0.3Sn negative electrode current collector of aqueous zinc-ion battery can be -2 The current condition remains stable for more than 1600 cycles.

[0037] Example 3

[0038] Preparation method of Cu-16.6Zn-0.3Sn negative electrode current collector for aqueous zinc ion battery, Figure 1 As shown, the following steps are included:

[0039] (1) Weigh 831 g of copper, 166 g of zinc, and 3 g of tin respectively;

[0040] (2) placing metal copper, zinc and tin into a graphite crucible, smelting them in a vacuum device at 950° C. for 0.5 h, and then casting and cooling to room temperature to obtain a Cu-16.6Zn-0.3Sn alloy ingot;

[0041] (3) Cutting the Cu-16.6Zn-0.3Sn alloy ingot into 3 mm thick alloy sheets;

[0042] (4) After the alloy sheet was rolled to 90 μm at one time, it was annealed at 450°C for 4 h and naturally cooled to room temperature in an argon and hydrogen atmosphere to prepare the Cu-16.6Zn-0.3Sn negative electrode current collector for the ternary alloy aqueous zinc ion battery.

[0043] The prepared aqueous zinc ion battery negative electrode current collector Cu-16.6Zn-0.3Sn was subjected to XRD and SEM tests. Figure 2 As shown, similar to Example 1, the alloy has a single-phase structure, and with the increase of zinc content, the diffraction angles corresponding to the three strong peaks shift relatively to the left, indicating that the zinc element has solid solution in the alloy matrix, resulting in a change in its lattice constant, as shown in Table 1;

[0044] Figure 5 This is the morphological characteristics and element distribution diagram of the negative electrode current collector Cu-16.6Zn-0.3Sn of the aqueous zinc ion battery. It can be seen that the grains contain a large number of equiaxed crystals and a small amount of twins. The grain size is 7 to 10 μm, and the twin area fraction is 1.2 to 4.5%.

[0045] The negative electrode current collector Cu-16.6Zn-0.3Sn of aqueous zinc ion battery was tested.

[0046] 5.75 g ZnSO4·7H2O was weighed and 7.48 mL deionized water was added to prepare a 2 M ZnSO4 electrolyte. The Cu-16.6Zn-0.3Sn negative electrode current collector of the aqueous zinc ion battery prepared in Example 3 was assembled with commercial zinc foil into a half-cell. -2 、1mAh cm -2 The coulombic efficiency and cycle stability were tested under the following conditions: Figure 7 As shown in the figure, the half-cell of aqueous zinc-ion battery negative electrode current collector Cu-16.6Zn-0.3Sn can be -2 The current condition remains stable for more than 2500 cycles.

[0047] Example Example 1 Example 3 Alloy Nominal Composition Cu-9.1Zn-0.3Sn Cu-16.6Zn-0.3Sn Lattice parameter a(0.1nm) 3.6242 3.6434

[0048] Table 1 Calculated values ​​of alloy lattice parameters of Examples 1 and 3

[0049] Example 4

[0050] An aqueous zinc ion battery,

[0051] The present invention also provides the application of the above-mentioned negative electrode current collector in an aqueous zinc ion battery. The prepared negative electrode current collector of the aqueous zinc ion battery is used as the negative electrode current collector of the zinc ion battery to assemble an aqueous zinc ion battery. Figure 4 As shown, the aqueous zinc ion battery comprises a positive electrode, a separator, an electrolyte, a negative electrode and an aqueous zinc ion battery negative electrode current collector of the present invention assembled in sequence, and the aqueous zinc ion battery negative electrode current collector comprises Cu-9.1Zn-0.3Sn and Cu-16.6Zn-0.3Sn. The positive electrode active material in the positive electrode comprises at least one of a manganese-based material, a vanadium-based material and a Prussian blue analog. The separator is a glass fiber separator. The electrolyte is a zinc salt aqueous solution, and the electrolyte is preferably at least one of zinc sulfate, zinc chloride, zinc acetate, zinc trifluoromethanesulfonate, manganese acetate and manganese sulfate.

[0052] Comparative Example 1

[0053] Preparation of pure copper current collector,

[0054] Only pure copper was used as the raw material, and the same preparation method as in Example 1 was used to prepare a pure copper current collector.

[0055] The test method of the pure copper current collector of Comparative Example 1 is the same as that of Example 2. The cycle test diagram is as follows: Figure 8 As shown, 5mAcm -2 The current condition remains stable for 80 cycles.

[0056] The two current collectors of Examples 1 and 3 proposed in the present invention are -2 The half-cell cycle times under current conditions are better than those of pure copper current collectors, among which the Cu-16.6Zn-0.3Sn current collector has the best effect on improving the cycle performance, as shown in Table 2.

[0057] Example Example 1 Example 3 Comparative Example 1 Alloy Nominal Composition Cu-9.1Zn-0.3Sn Cu-16.6Zn-0.3Sn Cu Half-cell stable cycle number 1600 2500 80

[0058] Table 2 Comparison of current collector performance between the embodiment and the comparative example.

Claims

1. Aqueous zinc ion battery negative electrode current collector, prepared by vacuum melting, rolling and annealing to obtain a ternary alloy, characterized in that: The composition includes 83.1-90.6wt% copper, 9.1-16.6wt% zinc, 0.2-0.4wt% tin and inevitable impurity elements. The ternary alloy has a single-phase structure, the alloy elements exist in the form of solid solution, zinc and tin are solid-solved in the alloy matrix, a large number of equiaxed crystals and a small amount of twins are distributed inside the grains, the grain size is 7 to 10 μm, the twin area fraction is 1.2 to 4.5%, and XRD characterization shows no characteristic peaks other than copper and zinc.

2. The negative electrode current collector of an aqueous zinc ion battery according to claim 1, characterized in that: The invention comprises, by mass percentage, 83.1-90.6wt% of copper, 9.1-16.6wt% of zinc, 0.3wt% of tin, and inevitable impurity elements.

3. The negative electrode current collector of an aqueous zinc ion battery according to claim 1, characterized in that: 906g of copper, 91g of zinc and 3g of tin were taken in weight proportion, and the negative electrode current collector Cu-9.1Zn-0.3Sn for aqueous zinc ion battery was prepared through vacuum melting, rolling and annealing. Zinc and tin elements were dissolved in the alloy matrix, and the grain size was 7-10μm. A large number of equiaxed crystals and a small amount of twins were distributed inside the grains, and the area fraction of twins was 1.2-4.5%.

4. The negative electrode current collector of an aqueous zinc ion battery according to claim 1, characterized in that: 831g of copper, 166g of zinc and 3g of tin were taken in weight proportion, and the negative electrode current collector Cu-16.6Zn-0.3Sn of aqueous zinc ion battery was prepared through vacuum melting, rolling and annealing. Zinc and tin elements were dissolved in the alloy matrix, and the grain size was 7-10μm. A large number of equiaxed crystals and a small amount of twins were distributed inside the grains, and the area fraction of twins was 1.2-4.5%.

5. A method for producing a negative electrode current collector for an aqueous zinc ion battery, characterized in that: Step S1: Vacuum melting, 83.1-90.6wt% of metal copper, 9.1-16.6wt% of metal zinc, and 0.2-0.4wt% of metal tin are placed in a graphite crucible and vacuum smelted in a vacuum smelting furnace. The vacuum degree during the vacuum smelting process is 10-200°. -5 mbar, the melting temperature in the vacuum melting process is 500~1100℃, and the melting time in the vacuum melting process is 0.5~2h. After cooling to room temperature, an alloy ingot is obtained; Step S2: Cutting, cutting the alloy ingot into alloy sheets with a thickness of 3 to 30 mm. Step S3: rolling-annealing, The alloy sheet is rolled to obtain an alloy foil with a thickness of 90 to 150 μm. The alloy foil is annealed at a temperature of 400 to 500°C for 4 to 5 hours. After the annealing, the alloy foil is naturally cooled to room temperature in an argon and hydrogen atmosphere to obtain an aqueous zinc ion battery negative electrode collector with a thickness of 90 to 150 μm.

6. The negative electrode current collector of an aqueous zinc ion battery according to claim 5, characterized in that: The step S1: putting 83.1-90.6wt% of metal copper, 9.1-16.6wt% of metal zinc, and 0.2-0.4wt% of metal tin into a graphite crucible.

7. The negative electrode current collector of an aqueous zinc ion battery according to claim 5, characterized in that: The aqueous zinc ion battery negative electrode collector Cu-9.1Zn-0.3Sn was prepared.

8. The negative electrode current collector of an aqueous zinc ion battery according to claim 5, characterized in that: The aqueous zinc ion battery negative electrode collector Cu-16.6Zn-0.3Sn was prepared.

Citation Information

Cited By

  • Multi-layer sandwich structure zinc negative electrode, preparation method and aqueous zinc ion battery

    CN120878769A